Diseño de instrumento para el estudio de dotación del personal de enfermería profesional y auxiliar del área médico-quirúrgica en siete instituciones de salud privadas Medellín 1994 (1997)
ABSTRACT: Our health system doesn´t have a method that permits an adequate dotation of professional and auxiliary nursing personnel in the medical and surgical services. The research sought to precise the functions realized by professional nurses and practical nurses during their shifts and according to the needs of patients and the politics of the institution. With the foundation the group designed a method adequate to provide the personnel in the medical and surgical services that seeks to improve the quality of care.